Mineral coated microparticles doped with fluoride and complexed with mRNA prolong transfection in fracture healing - Nelson, Anna Laura; Fontana, Gianluca; Chubb, Laura; Choe, Josh; Williams, Katherine; Regan, Dan; Huard, Johnny; Murphy, William; Ehrhart, Nicole; Bahney, Chelsea (Frontiers in Bioengineering and Biotechnology, 2024)
Impaired fracture healing, specifically non-union, has been found to occur up to 14% in tibial shaft fractures. The current standard of care to treat non-union often requires additional surgeries which can result in long recovery times. Injectable-based therapies to accelerate fracture healing have the potential to mitigate the need for additional surgeries. Gene therapies have recently undergone significant advancements due to developments in nanotechnology, which improve mRNA stability while reducing immunogenicity. In this study, we tested the efficacy of mineral coated microparticles (MCM) and fluoride-doped MCM (FMCM) to effectively deliver firefly luciferase (FLuc) mRNA lipoplexes (LPX) to a fracture site. MCM-LPX-FLuc and FMCM-LPX-FLuc were not found to cause any cytotoxic effects when tested in vitro. When measuring the osteogenic potential of each mineral composition, FMCM-LPX-FLuc trended higher in osteogenic markers through qRT-PCR than the other groups tested in a murine fracture and stabilization model, yet no significance was observed. Localized and systemic inflammation were measured through gene expression, histopathology scoring and measuring Creactive protein (CRP) in the serum. Despite FMCM-LPX-FLuc showing slightly elevated il-1β and il-4 levels in the fracture callus, inflammation scoring of the fracture callus did not result in any differences. Additionally, an acute systemic inflammatory response was not observed in any of the samples tested. The concentration of MCM-LPX-FLuc and FMCM-LPX-FLuc that was used in the murine fracture model did not stimulate bone when analyzed through stereological principles. Using reporter gene, firefly luciferase mRNA, transfection efficacy and kinetics of delivery platforms revealed that FMCM-LPX-FLuc prolongs the luciferase signal both in vitro and in vivo. These data together reveal that FMCM-LPX-FLuc could serve as a promising mRNA delivery platform for fracture healing applications.